Thermal regime in wheat growing regions of India - ., JAIPAL; DIKSHIT, S. K.; JOSEPH, LAWRENCE (MAUSAM, 1984)
The paper presents a study of various temperature parameters for the entire wheat zone of India. By taking into account the accepted heat requirements of the wheat crop, optimum periods for sowing and harvesting in different parts of the wheat zone have been assessed on the basis of long term data of temperature, its derived parameters and their distribution over the wheat zone (area), The periods for sowing, as assessed climatologically, generally fit in well with those obtained experimentally for certain areas.